2016
DOI: 10.1161/jaha.116.004336
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Vasospastic Angina Patients Presenting With Acute Coronary Syndrome

Abstract: BackgroundCoronary vasospasm is an important pathogenesis of acute coronary syndrome (ACS). However, the clinical features and prognosis of vasospastic angina (VA) patients presenting with ACS (VAACS) are still unclear. We aimed to evaluate the clinical characteristics and long‐term outcomes of VAACS patients without significant coronary artery stenosis.Methods and ResultsA total of 986 VA patients confirmed by ergonovine provocation test were analyzed. VAACS was defined as VA patients visiting the emergency r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 18 publications
0
23
0
2
Order By: Relevance
“…We report three cases of OHCA due to RCA spasm in the presence of non-obstructive coronary artery disease in men over the age of 65 years. Significant predictors of MACE in CSA patients are (1) history of OHCA, (2) organic coronary stenosis, (3) multivessel spasm, (4) ST-segment elevation during angina, (5) smoking, (6) angina at rest alone, and (7) beta-blocker use [4][5][6][7][8]. The incidence of OHCA in Japanese CSA patients was 2.4%, which is 50-fold higher than that in the general population [9,10].…”
Section: Discussionmentioning
confidence: 97%
“…We report three cases of OHCA due to RCA spasm in the presence of non-obstructive coronary artery disease in men over the age of 65 years. Significant predictors of MACE in CSA patients are (1) history of OHCA, (2) organic coronary stenosis, (3) multivessel spasm, (4) ST-segment elevation during angina, (5) smoking, (6) angina at rest alone, and (7) beta-blocker use [4][5][6][7][8]. The incidence of OHCA in Japanese CSA patients was 2.4%, which is 50-fold higher than that in the general population [9,10].…”
Section: Discussionmentioning
confidence: 97%
“…It is important to recognize that this score was developed and validated in an East Asian population and to date its applicability to other ethnicities is not known. Patients with VSA who initially present as an acute coronary syndrome may also represent a group at higher risk for recurrent infarction 13 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, another recent retrospective Korean cohort study by Cho et al. [ 22 ] described the follow-up in a large cohort of patients with vasospastic angina, as diagnosed with ergonovine provocation testing, presenting with ACS versus patients presenting without ACS. The study concluded that patients initially presenting with ACS had an increased risk of recurrent myocardial infarction and rehospitalisation because of recurrent angina.…”
Section: Discussionmentioning
confidence: 99%